Peripheral Arterial Disease and Risk of Atrial Fibrillation and Stroke: The Multi‐Ethnic Study of Atherosclerosis - O'Neal, Wesley T. (J Am Heart Assoc, 2014)
BACKGROUND: Peripheral arterial disease (PAD) shares several risk factors with atrial fibrillation (AF), and persons with PAD have an increased risk of stroke. It is unclear if PAD is associated with an increased risk for AF and whether this potential association explains the increased risk of stroke observed in those with PAD. METHODS AND RESULTS: We examined the association between PAD, measured by ankle‐brachial index (ABI), and incident AF and incident stroke, separately, in 6568 participants (mean age 62±10 years, 53% women, 62% nonwhite) from the Multi‐Ethnic Study of Atherosclerosis (MESA). ABI values <1.0 or >1.4 defined PAD. AF was ascertained through review of hospital discharge records and from Medicare claims data until December 31, 2010. An independent adjudication committee ascertained stroke events. Cox regression was used to estimate hazard ratios and 95% CIs for the association between PAD and AF and stroke. Over a median follow‐up of 8.5 years, 301 (4.6%) participants developed AF and 140 (2.1%) developed stroke. In a model adjusted for sociodemographics, cardiovascular risk factors, and potential confounders, PAD was associated with an increased risk of AF (hazard ratio 1.5, 95% CI 1.1 to 2.0). In a similar model, PAD was associated with incident stroke (hazard ratio 1.7, 95% CI 1.1 to 2.5), and the magnitude of risk was not different after inclusion of AF as a time‐dependent covariate (hazard ratio 1.7, 95% CI 1.1 to 2.5). CONCLUSIONS: PAD is associated with an increased risk of AF and stroke in MESA. Potentially, the relationship between PAD and stroke is not mediated by AF.